Efecto del cilantro (Coriandrum sativum) en polvo como agente de control microbiano en pasta de maní (Arachis hypogaea L.) a diferentes temperaturas de almacenamiento - Cantos Loor, Carlos Eduardo (2014)
The objective of this research was to determine the effect of coriander powder on microorganisms in peanut paste stored at different temperatures. Statistical linear regression analysis was applied for microbiology testing of all treatments, the influence of different concentrations of coriander powder and storage temperatures using the following levels (4% coriander powder at 10°C); (4% coriander powder at temperature environment); (8% coriander powder at 10°C); (8% coriander powder at temperature environment); (12% coriander powder at 10°C); (12% coriander powder at room temperature). The experimental unit was comprised in 3500g of peanut paste with coriander; in a period of 40 days with the following variables (E. coli, Salmonella sp., molds and yeasts), sensory analysis was evaluated with scoring test, evaluating the degree of acceptability in appearance, texture, aroma and flavor by a panel of 30 untrained tasters. The results of the control molds and yeasts performed the kinetic curve which showed a linear trend increased by day at 3.2x〖"10" 〗^"3" UPC / g, up to the 40th day with 2.0 x 2.0 x〖"10" 〗^"4 " UPC / g, there was no growth treatments giving linear trend 0, E. coli and Salmonella sp. treatments did not grow for 40 days while the control of the presence of microorganisms. In sensory analysis treatment T2 was the best in all the variables.